ESTATE, BORDER AND AGRICULTURAL EXPANSION IN THE SOUTH OF THE KINGDOM OF VALENCIA. THE VILANOVA LINEAGE DURING THE FIRST HALF OF THE 14 CENTURY. - CABEZUELO, JOSÉ VICENTE (Imago Temporis. Medium Aevum, 2019)
In this paper we will analyse the history of the lineage Vilanova in the kingdom of Valencia from the end of the 13 century until midway through the 14 century. We will focus on the methods used by the noblemen in the construction of the borders of the kingdom right up to the critical point mid century when the arrival of the Muslim population triggered political change.